A case of focal nodular hyperplasia with growth progression during pregnancy - Min Ji Kim; Sang Young Han; Yang Hyun Baek; Sung Wook Lee; Hee Jin Kwon (Clinical and Molecular Hepatology, 2014)
Focal nodular hyperplasia (FNH) is the second most common benign solid tumor of the liver and is usually found in young females. In FNH, spontaneous bleeding or rupture rarely occurs and malignant transformation is unlikely. The etiology of FNH is unclear, but because of female predominance and young age at onset, it seems that female hormone has an important role for the development of FNH. Although the development and the complications of hepatocellular adenomas have been related to the use of oral contraceptives and pregnancy, the influence of oral contraceptives and pregnancy on the growth and complications of FNH is controversial. Most FNH are stable in size and rarely complicated during pregnancy. We describe here a case of FNH with growth progression during pregnancy in a 27-year-old female. Her course of pregnancy and delivery was uneventful. Two months after delivery, the size of FNH was decreased.